Factors influencing training success in guide dogs and the development of novel behavioural assessments - Blythe, Simon (2020)
With demand growing for different types of working dogs, such as police and army dogs, the need to identify accurate behavioural profiling assessment models to aid the selection of puppies and young adult dogs, has never been more keenly sought. The comparatively recent and rapid emergence of the assistance dog sector (assistance dogs are trained to aid disabled persons carry out tasks that will improve their quality of life and independence), has added still further in the quest to find improved selection tests.